(untitled) (A Luz em Cena: Revista de Pedagogias e Poéticas Cenográficas, 2021)
The article proposes to make a reflection through an experience report on the creative process of light in the scenographic composition. Since the light, in some cases, complements a scenario, presenting itself and becoming the scenography itself. Thus, it is considered pertinent to expose procedures used for the construction of lighting in the reported shows. To this end, a historical and theoretical survey of the relationship between lighting and scenography is presented, based on the authors Appia (1962), Tudella (2018), Forjaz (2008) and Camargo (2012). Such discussion proposes a dialogue between the mentioned authors, the creative processes of four shows that work with lamps, instruments and shadows as scenography and light as a scenographic effect.